Novel inorganic pyrophosphatase from soil metagenomic and family and subfamily prediction - Rodrigues, Gisele Regina [UNESP]; Val-Moraes, Silvana Pompeia [UNESP]; Lemos, Eliana Gertrudes Macedo [UNESP]; Pizauro Júnior, Joao Martins [UNESP] (Scientific Research Publishing, 2014)
Inorganic pyrophosphatase (PPase) is widely studied, to be extremely important for survival of plants and microorganisms. PPases catalyze an essential reaction the hydrolysis of inorganic pyrophosphate (PPi) to inorganic phosphate (Pi). Studies involving the mechanism of PPase were performed in microorganisms culture. We didn’t found reports of PPase derived from soil metagenomic libraries. Soil environment has immense diversity of microorganisms, yet most remains unexplored and the metagenome are the technologies used and investigate uncultured microorganisms potential. The aim is to identify novel genes using the metagenomic approaches from a bioinformatics perspective and hopefully will serve as a useful resource. With this purpose, we used the metagenomic library of Eucalyptus spp. arboretum (EAA). We did a screening to select a positive clone and submitted them to the process of shotgun. The data obtained was submitted to bioinformatics analyses. These analyses identified were the novel MetaPPase gene and were classified according to the predict family and subfamily.
Keywords: Soil Diversity; Bioinformatic; Structure; Membrane Protein; Ion Transport; metagenômica; pirofosfatase; translocador de H+